ANALISIS SISTEM INFORMASI MANAJEMEN ADMINISTRASI LAUNDRY BERBASIS WEB - Fiqih Ismawan; Abdurahman Abdurahman (Universitas Muhammadiyah Jakarta, 2022)
The proliferation of laundry services lately has been found in every corner of the city even to get to the village, the number of laundry services nowadays is due to the desire of people to look for instant and fast washing clothes and become a necessity. The services offered are very diverse, ranging from those using the package system, to using the kilo system even unit services. Various attractive offers are provided by laundry businesses to attract consumers. Most laundry services are home-based businesses, so the management is done manually and have not used a computerized system from the transaction to the process of taking clothes that are washed, where each consumer comes to the reception section. others are still handwritten. This is certainly not practical, because it takes a lot of time and the loss of the note which results in inefficient transaction systems in the laundry. This study aims to help laundry services in developing their business and creating efficiency in dealing with customers. The method that will be used is the prototyping method in implementing and building system applications with the help of PHP MySQL software. The results of this research are localhost web-based laundry administration information system application.